Characteristics of Analogue Rice Based on Taro (Colocasia sp.) From Mentawai Islands Regency with a Mixture of Mocaf and Soybean Flour (Glicine max l.) - Samosir, Joni Frengki; Kasim, Anwar; Kasim, Fitriani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Research on the manufacture of taro-based analogue rice with a mixture of soy flour and mocaf as a food diversification in an effort to reduce the large consumption of rice in Indonesia has been carried out. The purpose of this study was to obtain the most appropriate formulation of a mixture of taro, soybean flour, and mocaf for making analog rice. This study used a completely randomized design (CRD) method where the treatments used were different formulations of soybean flour at 4 levels (10%, 20%, 30%, and 40%) and mocaf flour at 4 levels (40%, 30%, 20%, and 10%). The results showed that the closest analog rice formulation in terms of chemical and physical characteristics based on the SNI Standard for rice was found in formulation C, namely 50% taro, 30% soybean flour, and 20% mocaf. The chemical characteristics of the analog rice are starch content of 37.72%, amylose 14.88%, amylopectin 22.84%, protein 14.09%, fat 10.64%, dietary fiber 22.70%, energy value of 407.63 kcal, 2.92% ash, 63.87% carbohydrates, and 8.48% moisture content. The best physical characteristics of analog rice are hardness (130.36 N/cm2), medium length and shape, and one thousand grain weight (15.93 g).